Editorial: Molecular epidemiology and phylogeny of tick-borne pathogens in ixodid ticks and vertebrate hosts - Aktas, Munir; Altay, Kursat (Frontiers Media Sa, 2024)
[Abstract Not Available]
Keywords: ixodid ticks; tick-borne diseases; molecular detection; epidemiology; phylogeny